PENGABDIAN PEMERIKSAAN MATA USIA SEKOLAH DI MTS AL WATHONIAH KOTA SEMARANG JAWA TENGAH - Kholil, Mochammad (Jurnal Implementasi Pengabdian Masyarakat Kesehatan (JIPMK), 2022)
Refractive error is a condition in which parallel rays that enter the eyeball are refracted by the refractive medium incorrectly on the retina. (1) Refractive errors in the eye consist of myopia, hypermetropia, astigmatism. Myopia is a condition in which parallel rays entering the eyeball are refracted by the refractive media in front of the retina. Refractive errors can be corrected by using glasses, contact lenses, and currently refractive surgical procedures such as excimer laser, such as LASIK can be performed. The purpose of this research is to provide counseling about eye health to students of SMP Al - Wathoniyah Semarang so that they can find out about eye health at school age in eye health services in the city of Semarang.The method of this research is to use the lecture method for further examination of the student's refraction. The service is done by providing material on eye health at school age and the prevention of refractive errors. The target is all students of SMP Al-Wathoniyah Semarang. The results of the study, this activity began with coordination with the SMP Al Wathoniyah Semarang, the service was carried out for 50 students, with high enthusiasm from many questions from students. And the provision of glasses for Al Wathoniyah students who have refractive errors.The report of the results of this service, from 50 students examined, there were 16 refractive errors of Astigmatism, and 34 students with Myopia refractive disorders.